(untitled) (Philologia, 2021)
On the basis of the short analysis and semantic classiﬁcation of nicknames of speakers of Serbian used while chatting on the Internet, we notice that besides real nicknames (originally used in the intimate sphere of everyday communication), nicknames with different modiﬁcations based mostly on graphic, structural creations (acronyms, reduplications of graphemes or the names, anagrams, rebuses, combinations of sign systems etc.) are used for the Internet. The latter turn into semantically transparent and semantically non-transparent pseudonyms. The form of pseudonyms used on the Internet ﬁts into the traditional deﬁnition of the pseudonym, but there are certain innovations in the functioning of pseudonyms in the new way of communication. Unlike pseudonyms in the traditional sense, which lack inﬂuence on the interlocutor because possessors of the pseudonyms don’t take part in the communication directly, the pseudonyms of the users of the Internet have an active inﬂuence on the interlocutor in order to establish succesful communication. Considering the structure, we notice two basic principles of creating nicknames/pseudonyms of the users of the Internet: the principle of the language and communicative game and the principle of hiding.